MODULE’S INFLUENCE ON BASIC ENGINEERING MECHANICS’S LEARNING OUTCOMES OF CIVIL ENGINEERING STUDENTS - Muhammad Rahman Rambe; Pohan, Rizky Febriani (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Modules are teaching materials that contain learning objectives, learning material/substance and evaluation so that students can learn independently and be more active in learning. The purpose of this study was to determine the effect of using the module on student learning outcomes in first semester of the Civil Engineering Study Program, Faculty of Engineering, Graha Nusantara University in the Basic Engineering Mechanics course and the magnitude of the increase in learning outcomes. The research method used was quasi-experimental method with a pretest-posttest control group design. The number of samples is 40 students, which are divided into two groups. Data collection uses test techniques (questions) through pre-test and post-test. Data processing was performed using Statistical Product and Service Solution (SPSS) version 21.0 for Windows. Based on the results of the t-test, it was found that tcount ≥ ttable or 4.2058 ≥ 2.023 meaning that Ho is rejected or Ha is accepted. So that the module-based learning model affects the learning outcomes of Basic Engineering Mechanics students of the Civil Engineering Study Program, Graha Nusantara University Padangsidimpuan with an increase in learning outcomes of 41.86%. Meanwhile, the conventional learning model is only able to increase the learning outcomes of Basic Engineering Mechanics by 28.69%. The module-based learning model has a percent effectiveness of 35.19% to improve Basic Engineering Mechanics learning outcomes. Thus, the application of a module-based learning model is very suitable and effective for colleges used.